Domain-Specific Platform Alignment Predicts EFL Proficiency at an Indonesian University - Nofvia De Vega; Jhoni Eppendi; Syarifa Rafiqa (Script Journal: Journal of Linguistics and English Teaching, 2026)
Background:  This study examines how four mobile-cloud platforms, BeL (reading), FlipGrid (speaking), Padlet (writing), and VoiceThread (listening), were integrated into EFL instruction through a domain-platform alignment model at a 3T-region Indonesian university. The study compares domain-level contributions to composite proficiency and does not claim to isolate platform-specific causal effects. Methodology:  A quasi-experimental pre-test and post-test design was employed with 55 university students in advanced language courses. Stratified random sampling ensured proficiency-level representation. A 12-week structured intervention assigned each platform to one skill domain. Four participants were excluded for completing fewer than 80% of tasks, yielding a final sample of 51. Multiple linear regression was applied following verification of classical assumptions. Findings:  The regression model was statistically significant (R = 0.960, R² = 0.921, F = 146.27, p < .001), with all four domain scores significant at p < .001. The R² value is largely expected given that the Total Language Proficiency Score is mathematically derived from the same four domain predictors, reflecting a compositional rather than independent predictive relationship. Standardized coefficients indicated reading as the strongest contributor (β = .433), followed by listening (β = .371), writing (β = .367), and speaking (β = .356). Post-intervention score improvements are reported as descriptive observations only, as no separate inferential pre-test to post-test analysis per domain pairing was conducted. Conclusion:  These findings offer preliminary descriptive support for domain-differentiated platform use in 3T-region EFL higher education. Model explanatory power should be interpreted cautiously given the compositional constraint, and platform-specific causal claims require further experimental evidence. Originality:  This study introduces a structured domain-platform alignment model enabling principled, domain-level comparison of platform integration within a single EFL study design.